2020
DOI: 10.1557/jmr.2020.200
|View full text |Cite
|
Sign up to set email alerts
|

Studies on characterization, magnetic and electrochemical properties of nano-size pure and mixed ternary transition metal ferrites prepared by the auto-combustion method

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…46,47 Ferrite spinel of formula ABFe 2 O 4 consists of two divalent metal ions in which the ratio of these divalent ions may vary and are referred to as mixed ferrites. 48 The distribution of the cations in mixed ferrites significantly affects the surface properties of ferrospinels making them catalytically more active. Because of their small size and large z E-mail: leenar@cusat.ac.in number of cations for co-ordination sites, nanocrystallites are capable of enhancing the rate of chemical reactions and are increasingly gaining popularity.…”
mentioning
confidence: 99%
“…46,47 Ferrite spinel of formula ABFe 2 O 4 consists of two divalent metal ions in which the ratio of these divalent ions may vary and are referred to as mixed ferrites. 48 The distribution of the cations in mixed ferrites significantly affects the surface properties of ferrospinels making them catalytically more active. Because of their small size and large z E-mail: leenar@cusat.ac.in number of cations for co-ordination sites, nanocrystallites are capable of enhancing the rate of chemical reactions and are increasingly gaining popularity.…”
mentioning
confidence: 99%
“…The synthesis and characteristics of mixed cobalt-copper ferrites have been the subject of several papers during the last three years. As an illustration, Khairy et al [35] used the self-combustion process with urea as fuel to synthesize both pure and mixed ternary ferrite nanocrystallites Cu 0.5 Co 0.5 Fe 2 O 4 (CuCoF). They concluded that the magnetic, structural, and electrochemical characteristics of the ferrites that were produced were significantly influenced by the distribution of cations in the examined samples.…”
Section: Introductionmentioning
confidence: 99%
“…Materials based on transition metal ferrites are increasingly being used in various fields of science and technology due to their excellent magnetic, catalytic, and photo-and electrocatalytic properties, among others [1][2][3]. Application of nanoparticles of transition metal ferrites for magnetic resonance imaging, cancer diagnosis at the primary stage, magnetothermal, anticancer and antimicrobial therapies, hyperthermia, and drug delivery have been recently reviewed [4,5].…”
Section: Introductionmentioning
confidence: 99%